The relationship of five factor model of personality towards teacher's organizational commitment / Raja Faris Aliuddin Raja Alwi and Nur Azfar Abdul Aziz - Raja Alwi, Raja Faris Aliuddin; Abdul Aziz, Nur Azfar
Organizational commitment generally can be defined as a psychological or emotional contract that employees have with their organization. According to Allen & Mayer (1990), employee's commitment have three reasons. The first reason is emotional attachment. The second reason is the feeling of losing profit from the effort they made with the organization. Third is the feeling of responsible towards the organization. Organizational commitment has three components as proposed by Allen and Meyer (1990) which are affective commitment, continuance commitment, and normative commitment. Affective commitment means that employees stay with the organization because of their own will. Continuance commitment means that employees stay because they need to stay. And normative commitment means that employees stay because they feel it as their responsible. The higher the organizational commitment that the employee has, the lower the probability that the employee will leave the organization (Allen & Meyer, 1990).